Metagenomic Approaches to Explore the Quorum Sensing-Mediated Interactions Between Algae and Bacteria in Sequence Membrane Photo-Bioreactors - Wu, Xiaogang; Kong, Lingrui; Pan, Juejun; Feng, Yiming; Liu, Sitong (Frontiers in Bioengineering and Biotechnology, 2022)
Bacterial-algal water treatment is more effective for better harvesting and promotes energy savings than other traditional treatments, while the relationships between them are multifarious. Among all interactions, quorum sensing plays the essential ecological role. However, the relative contributions of signaling in the interaction between algae and bacteria are not clear. In order to elucidate the role of quorum sensing by indole-3-acetic acid (IAA) in terms of the algal-bacterial interaction during the nitrogen removal process, the bioreactors respectively inoculated with Chlorella, Phormidium and both of them were started. We manifest the existence of multiple signaling-related proteins by alignment with the constructed database, and the signaling was analyzed using metagenomic sequence data obtained during bioreactor operation. We found that IAA was mainly synthetized depending on indole-3-acetamide (IAM) and indole-3-pyruvic acid (IPA) pathways by calculating gene abundance of IAA-synthetase. Both Chlorella and co-culture reactor possessed higher nitrogen removal rate (NRR) than Phormidium reactor, and the abundance profile of signaling-related gene is similar with the NRR. The signaling-related gene abundance increased in Chlorella and co-culture reactors but decreased in Phormidium reactor. Pseudomonas, Hydrogenophaga and Zoogloea are the dominant signaled bacteria. Chlorella is the dominant signaled algae. The relative abundance of total signaled bacteria in the whole bacterial community increased during the start-up in Chlorella and co-culture reactors. According to the network analysis, phytoplankton prefers to positively correlate with signaled bacteria than non-signaled bacteria, which indicated that the signaling influences the algal-bacterial interaction. These findings hint at the significance of algal-bacterial signaling in this interkingdom interaction during nitrogen removal.